Thermal behavior of spiral fin-and-tube heat exchanger having fly ash deposit - Nuntaphan A. (2014)
This research investigates the effect of fly-ash deposit on thermal performance of a cross-flow heat exchanger having a set of spiral finned-tubes as a heat transfer surface. A stream of warm air having high content of fly-ash is exchanging heat with a cool water stream in the tubes. In this study, the temperature of the heat exchanger surface is lower than the dew point temperature of air, thus there is condensation of moisture in the air stream on the heat exchanger surface. The affecting parameters such as the fin spacing, the air mass flow rate, the fly-ash mass flow rate and the inlet temperature of warm air are varied while the volume flow rate and the inlet temperature of the cold water stream are kept constant at 10 l/min and 5 °C, respectively. >From the experiment, it is found that as the testing period is shorter than 8 h the thermal resistance due to the fouling increases with time. Moreover, the deposit of fly-ash on the heat transfer surface is directly proportional to the dust-air ratio and the amount of condensate on heat exchange surface. However, the deposit of fly-ash is inversely proportional to the fin spacing. The empirical model for evaluating the thermal resistance is also developed in this work and the simulated results agree well with those of the measured data. © 2006 Elsevier Inc. All rights reserved.